The Effect of Snowball Throwing Cooperative Learning Model on Student Learning Outcomes - Siti Irawahyuni; Pratiwi Pujiastuti; Aninditya Sri Nugraheni (AL-ISHLAH: Jurnal Pendidikan, 2021)
Snowball Throwing-style cooperative learning has been shown to impact primary school students' academic performance positively. This type of research is quasi-experimental. Documentation and testing methods are used to collect data. Before hypothesis testing using t-tests, the data analysis technique used descriptive analysis and prerequisite analysis tests such as initial ability, normality and homogeneity of variance tests. According to the findings, Indonesian subjects taught using the cooperative learning model of the snowball throwing type had an average score of 19,750, and those taught using the expository learning model had an average score of 17,578. The t-test yielded tcount = 3.114 and ttable = 2.026 as the final results. This means that Indonesian primary school students learn differently in classes taught using the snowball-throwing cooperative learning model and classes taught using expository learning models, according to the t-test results. Snowball Throwing type cooperative learning is more influential than expository learning on Indonesian for elementary school subject learning outcomes according to the results of t-tests.